Single Clove Garlic (Allium sativum) Essential Oil as an Inhibitor of Staphylococcus aureus Bacteria - Abdul Gofur; Ida Wulandari; M. Fitri Athoillah; Agung Witjoro; Sri Rahayu Lestari (Biosaintifika: Journal of Biology & Biology Education, 2019)
Staphylococcus aureus is gram-positive bacteria that often infect the skin. S. aureus has been experiencing resistance to several antibiotics. One of the solutions to overcome the resistance is by using garlic that is believed by the society can overcome bacterial infection. The study aimed to find out the influence of the variation in concentration of local single clove garlic essential oil used on the inhibition and damage of morphological structure of S. aureus bacteria. The inhibition test was conducted using disc diffusion method. The experiment groups consisted of 1% DMSO as negative control, vancomycin 30µg/ml as positive control and single clove garlic essential oil (25 mg/ml, 50 mg/ml, 75 mg/ml and100 mg/ml) as treatment groups. The diameter of inhibition zone was measured using calipers. The morphological damage of the bacterial cells can be seen using Scanning Electron Microscopy (SEM) with magnification of 25000x. The result of Kruskal-Wallis test analysis indicated that the extract of local garlic essential oil has inhibitory activities against S. aureus bacteria (P0.05). The damage to the morphological structure of bacterial cells with the administration of 30 µg/ml vancomycin was equal to 100 mg/ml single clove garlic essential oil extract. Single clove garlic essential oil can be used as an alternative treatment for skin infection diseases by inhibiting S. aureus growth.